2001
DOI: 10.1673/031.001.0401
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and physical analyses of wax ester properties

Abstract: Wax esters are major constituents of the surface lipids in many terrestrial arthropods, but their study is complicated by their diversity. We developed a procedure for quantifying isomers in mixtures of straight-chain saturated and unsaturated wax esters having the same molecular weights, using single-ion monitoring of the total ion current data from gas chromatography-mass spectrometry. We examined the biological consequences of structural differences by measuring the melting temperatures, Tm, of >60 syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 31 publications
(56 reference statements)
3
86
1
Order By: Relevance
“…These peaks were superimposed to a wide and large halo, indicating that the β'-crystals were very small and dispersed in a very large liquid phase. At −13 C, a temperature matching the onset temperature of crystallization of JLE-28 1 , several very sharp extra peaks appeared in the WAXD (Figure 2a). At least nine reflections associated with a triclinic subcell (β-phase) were unambiguously indexed ( Table 2).…”
Section: Crystal Phase Development Of Jle-28mentioning
confidence: 91%
See 3 more Smart Citations
“…These peaks were superimposed to a wide and large halo, indicating that the β'-crystals were very small and dispersed in a very large liquid phase. At −13 C, a temperature matching the onset temperature of crystallization of JLE-28 1 , several very sharp extra peaks appeared in the WAXD (Figure 2a). At least nine reflections associated with a triclinic subcell (β-phase) were unambiguously indexed ( Table 2).…”
Section: Crystal Phase Development Of Jle-28mentioning
confidence: 91%
“…They possess unique properties suitable for a wide variety of applications ranging from lubricants to cosmetics, medical formulations, and foods [1]. Monoesters, such as those found in jojoba oil, are known to be very functional as lubricants and performance waxes [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our studies showed that this percentage was lower in bees, ranging from 52% to 58% in Buckfast bees and from 46% to 55% in Caucasian bees in the total of this fraction. Honeybees and dragonflies contain up to 58% of cuticular wax esters and phenols, having a total of 36-50 carbon atoms (Jacob and Hanssen, 1979;Patel et al, 2001). In our studies, Caucasian and Buckfast bees had respectively 45 Body-surface compounds in honey bee Body-surface compounds in honey bee -54% and 42 -48% of C12 -C32 esters on their cuticles.…”
Section: Discussionmentioning
confidence: 45%